Behavior-Focused Alternative Schools: Impact on Student Outcomes. (February 2016) - Wilkerson, Kimber; Afacan, Kemal; Perzigian, Aaron; Justin, Whitney; Lequia, Jenna
Behavior-focused alternative schools serve students who have been unsuccessful in other school settings due to low academic achievement coupled with significant behavior challenges. In this study, we investigated the effectiveness of secondary behavior-focused alternative schools on four different student outcome variables: (a) school attendance, (b) credits earned, (c) number of office referrals, and (d) number of suspensions. Using longitudinal data from a large urban school district and propensity score matching, we examined the extent to which outcomes of secondary students attending behavior-focused alternative schools differed compared to a matched sample of students attending traditional secondary schools. Findings from Poisson regression analyses indicate that enrollment in a behavior-focused alternative school significantly predicts earning fewer credits in one semester, lower attendance, and a lower number of office referrals. Implications for policy, practice, and further research relative to these findings are discussed.